Depiction of Women in Early 20th-century Posters and Postcards - Collisová, Natalia Maria (Univerzita Pardubice, 2025)
This bachelor thesis examines the portrayal of women in British posters and postcards at the beginning of the 20th century. The first chapter provides a theoretical background on contemporary and Victorian gender stereotypes, the concept of the New Woman and the suffragette movement. The second chapter analyses the appearance of women in posters and postcards from the period, and the third chapter explores the activities women were depicted as engaging in.
Vyobrazení žen na plakátech a pohlednicích z počátku 20. století
Keywords: Británie; genderové stereotypy; hnutí sufražetek; Nová žena; plakáty; pohlednice; vyobrazení žen; Britain; gender stereotypes; New Woman; postcards; posters; suffragette movement; women's representation